Influencia de los factores ambientales en la prevalencia del pterigión en trabajadores agrícolas del sector Delia Cristina, La Unión, Babahoyo, octubre 2024- abril 2025. - Párraga Hurtado, Nahomy Nicole (2025)
Pterygium is an eye condition in which abnormal tissue grows over the conjunctiva and, in some cases, extends toward the cornea, potentially affecting vision over time. While is exact cause remains unknown, it has been linked to prolonged exposure to environmental factors such as solar radiation, dust, wind, and low humidity. These conditions are especially common among agricultural workers, particularly in tropical climates and rural areas. This research aims to examine how environmental conditions influence the prevalence of pterygium among agricultural workers in the Delia Cristina sector, located in the La Unión parish, Babahoyo canton, during the period from October 2024 to April 2025. A quantitative approach was used to conduct this study, employing a relational, observational, and explanatory design. The research was non-experimental, cross-sectional, and correlational. The sample consisted of 100 agricultural workers aged 30 to 50, selected to assess the impact of environmental factors on the development of pterygium. Data collection was carried out through surveys and observations. The results revealed a high prevalence of this ocular condition, with men being the most affected due to their greater exposure to solar radiation and other environmental elements associated with outdoor agricultural work. In conclusion, prolonged exposure to certain environmental factors- particularly UV radiation, wind, dust, and climate variations- plays a significant role in the development of pterygium. Additionally, a lack of awareness regarding prevention was identified among the population, highlighting the need to implement educational strategies and promote the use of protective eyewear to mitigate the impact of this condition.